Crime Story in the Macedonian Printed Daily Newspapers - Vesna, Stefanovska (International Journal of Criminology and Sociology, 2016)
The paper examines the media coverage of crime in the Macedonian printed newspapers and the way in which certain circumstances related to the offender, the victim and the crime are depicted. The content analysis is based on quantitative and qualitative data collected from the media articles within three-month period by using written coding instrument. The main findings indicate that there are different approaches to and prioritization of criminal offences worth publishing in daily newspapers. The latter exhibit uneven representation of violent compared to property crimes, which means that the former crimes compared to property felonies, although less frequent in occurrence, note higher representation in part of the newspapers. In addition, differences according to the place of crimes commission are noticed between media in Macedonian and Albanian. Albanian media tend to emphasize crime perpetrated in areas where majority population is of Albanian origin compared to other major municipalities in the country. In this way, one gets the impression that these areas are incomparably much more burdened with crime, which makes them less safe than other major municipalities. The findings relate only to media texts published in the printed newspapers on the research topic and to the classifications and definitions contained in criminal laws. Therefore, in-depth analysis on crime news depiction, not only in printed media, but also in electronic media in general, and at the web portals, in particular is challenging for scholars. This will bring new scientific insight into Macedonian criminological critical thoughts related to the role and meaning of the media and their discourse in construction of crime and criminality.